(untitled) (Revista Venezolana de Salud Pública, 2018)
Dengue is an acute febrile disease caused by four dengue virus (DENV) serotypes whose prevalence in the Americas has quintupled between 2003 and 2013. The immune response against the infection with dengue virus involves cellular and humoral factors. We performed an observational and cross-sectional study to evaluate the levels of interleukins of the innate immune response (IL-8, TNFα), TH1 response (IFNγ), TH2 (IL-13) and regulatory (IL-10) in serum of patients during the acute phase of infection with the DENV1, DENV3 and DENV4 serotypes.